Potential for Offspring with Varicocele and Pcos - Sayyidah Auliyaur Rohmah; Anisa WULANDARI; Farisa Aina FAHMA; Abdul Rois MURTADHO (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Infertility affects a significant portion of couples worldwide, with 30% of cases attributed to male factors, 30% to female factors, 30% to both partners, and 10% to unknown causes. This study focuses on two common causes of infertility: varicocele in men and Polycystic Ovary Syndrome (PCOS) in women. Varicocele, characterized by the enlargement of veins within the scrotum, disrupts spermatogenesis by increasing testicular temperature, leading to poor sperm quality. PCOS, affecting 5-10% of women of reproductive age, is marked by excessive androgen levels, irregular menstruation, and obesity, significantly raising the risk of infertility. Through case studies and literature review, this research highlights the potential for individuals with varicocele or PCOS to achieve pregnancy with appropriate treatment. The study aims to explore the specific examination and treatment processes required for these conditions and to provide insights into improving fertility outcomes for affected individuals.